2005
DOI: 10.1161/01.cir.0000152479.54298.51
|View full text |Cite|
|
Sign up to set email alerts
|

Brugada Syndrome: Report of the Second Consensus Conference

Abstract: Abstract-Since its introduction as a clinical entity in 1992, the Brugada syndrome has progressed from being a rare disease to one that is second only to automobile accidents as a cause of death among young adults in some countries. Electrocardiographically characterized by a distinct ST-segment elevation in the right precordial leads, the syndrome is associated with a high risk for sudden cardiac death in young and otherwise healthy adults, and less frequently in infants and children. Patients with a spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
818
0
29

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,641 publications
(881 citation statements)
references
References 137 publications
6
818
0
29
Order By: Relevance
“…The types of BrS were classified according to the ECG criteria described in the report of the second consensus conference, which defined type 1 as characterized by a coved‐type J point elevation ≥2 mm (0.2 mV) and non–type 1 as characterized by type 2 or 3 BrS ECG, that is, a saddleback‐type J point elevation ≥2 mm (0.2 mV) 3. Patients who had ECGs with J point elevation ≥0.2 mV in the right precordial leads and non‐BrS ECG were categorized as having STERP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The types of BrS were classified according to the ECG criteria described in the report of the second consensus conference, which defined type 1 as characterized by a coved‐type J point elevation ≥2 mm (0.2 mV) and non–type 1 as characterized by type 2 or 3 BrS ECG, that is, a saddleback‐type J point elevation ≥2 mm (0.2 mV) 3. Patients who had ECGs with J point elevation ≥0.2 mV in the right precordial leads and non‐BrS ECG were categorized as having STERP.…”
Section: Methodsmentioning
confidence: 99%
“…Brugada syndrome is a hereditary arrhythmogenic disease characterized by accentuated ST‐segment elevation (type 1) in the right precordial leads (V 1 through V 3 ) and increased risk of sudden cardiac death (SCD) without structural heart disease 1, 2, 3. The data from previous studies vary regarding prevalence and prognosis for patients with Brugada‐type ECG (BrS) because of different populations (eg, general population, office workers),4, 5, 6, 7, 8, 9 different ECG definitions,5, 6, 9, 10, 11, 12 relatively short‐term follow‐up,5, 6, 9, 10, 12, 13 or poorly defined SCD 5, 6, 7, 8, 10, 11, 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…After an injection of a sodium channel blocker, the J waves in BrS become more prominent, while those in ERS either do not change or become attenuated. The Brugada Consensus Report proposed that a sodium channel blockade is required to diagnose BrS in the absence of a coved‐type ST‐segment elevation 2. Moreover, some reports have demonstrated that the J waves in BrS are concealed by CRBBB 8, 9.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of sodium channel blockers on the J waves differ greatly between ERS and BrS 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation